Climatic control of forest herb seed banks along a latitudinal gradient. Issue 10 (27th May 2013) - Plue, Jan; De Frenne, Pieter; Acharya, Kamal; Brunet, Jörg; Chabrerie, Olivier; Decocq, Guillaume; Diekmann, Martin; Graae, Bente J.; Heinken, Thilo; Hermy, Martin; Kolb, Annette; Lemke, Isgard; et al.
Abstract: Aim: Seed banks are central to the regeneration strategy of many plant species. Any factor altering seed bank density thus affects plant regeneration and population dynamics. Although seed banks are dynamic entities controlled by multiple environmental drivers, climatic factors are the most comprehensive, but still poorly understood. This study investigates how climatic variation structures seed production and resulting seed bank patterns. Location: Temperate forests along a 1900 km latitudinal gradient in north‐western (NW) Europe. Methods: Seed production and seed bank density were quantified in 153 plots along the gradient for four forest herbs with different seed longevity: Geum urbanum, Milium effusum, Poa nemoralis and Stachys sylvatica . We tested the importance of climatic and local environmental factors in shaping seed production and seed bank density. Results: Seed production was determined by population size, and not by climatic factors. G . urbanum and M . effusum seed bank density declined with decreasing temperature (growing degree days) and/or increasing temperature range (maximum–minimum temperature). P . nemoralis and S . sylvatica seed bank density were limited by population size and not by climatic variables. Seed bank density was also influenced by other, local environmental factors such as soil pH or light availability. Different seed bank patterns emerged due to differential seed longevities. Species with long‐lived seeds maintained constant seed bank densities by counteracting the reduced chance of regular years with high seed production at colder northern latitudes. Main conclusions: Seed bank patterns show clear interspecific variation in response to climate across the distribution range. Not all seed banking species may be as well equipped to buffer climate change via their seed bank, notably in short‐term persistent species. Since the buffering capacity of seed banks is key to species persistence, these results provide crucial information to advance climatic change predictions on range shifts, community and biodiversity responses.